Defensive versus evidence-based medical technology: Liability risk and electronic fetal monitoring in low-risk births. (January 2023) - Roth, Louise Marie
Abstract: Technology-intensive birth practices are a hallmark of the overmedicalization of birth. For example, obstetricians routinely use continuous electronic fetal monitoring (EFM), even though this technology is not evidence-based, has a high rate of false positives, and does not improve outcomes in low-risk deliveries. Providers often argue that they must use EFM to protect themselves from malpractice liability, making it a form of defensive medicine. But does variation in actual liability risk contribute significantly to the use of non-evidence-based medical technology like EFM? This study uses multi-level logistic models to examine the effects of malpractice laws and lawsuits on EFM in low-risk births from 1995 to 2003. The models test the hypothesis that state-level variation in liability risk should influence the probability of EFM use. The models reveal that the probability of reporting EFM is higher when states artificially reduce liability risk by capping damage awards, suggesting that objective liability risk does not promote routine EFM and may deter it. In fact, caps on damages limit providers' legal exposure without doing anything to encourage higher quality care. It is possible that states without tort reforms place greater emphasis on patient rights, safety, and quality of care. On the other hand, by reducing liability risk without encouraging improvements in quality, tort reform laws may inadvertently promote more technology use. Highlights: Continuous electronic fetal monitoring is not evidence-based for low-risk births. Providers often say that they must use EFM to defend against malpractice claims. Practices like continuous EFM represent poorer quality, assembly-line care. Non-evidence-based technologies are more common when tort reforms reduce liability risk.